KENEKARAGAMAN JENIS GASTROPODA PADA ZONA INTERTIDAL DI PANTAI TERES AMARASI SELATAN KABUPATEN KUPANG - Denseyana Malo; Maya Fitriani Roman, Nardi Matias Leo (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Research on Gastropod Species Diversity in the Intertidal Zone at Teres Beach, South Amarasi District, Kupang Regency was conducted from March to April 2024. The purpose of the study was to determine the types of gastropods in the intertidal zone, the diversity of gastropod species in the intertidal zone, to determine the environmental parameters that support the life of gastropod species in the intertidal zone. The method used was purposive sampling. Sampling was done at the lowest tide. The type of subtraction is rocky and sandy. The station consists of 2 stations, where each station is located 3 transect lines, on each transect line made 5 plots with a size of 3x3 with a distance of 2 metres between the plots. Data analysis using the Shannon Wiener diversity formula . The results of the study found 7 species with a total of 168 individuals. Diversity ranged from 0.2464-0.3267Ind/m2. The conclusion is that the diversity of gastropods on Teres beach in South Amarasi is low with a diversity index value of 0.2670\m2